2022
DOI: 10.3389/fimmu.2022.845867
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Immunity in Lung Transplant Rejection - Effector Mechanisms and Therapeutic Implications

Abstract: Allograft rejection remains the major hurdle in lung transplantation despite modern immunosuppressive treatment. As part of the alloreactive process, B cells are increasingly recognized as modulators of alloimmunity and initiators of a donor-specific humoral response. In chronically rejected lung allografts, B cells contribute to the formation of tertiary lymphoid structures and promote local alloimmune responses. However, B cells are functionally heterogeneous and some B cell subsets may promote alloimmune to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 126 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…Due to the fact that B cells have multiple functions, including immunoglobulin production, cytokine production, and antigen presentation, therapeutic approaches targeting B-cells are important for controlling AMR [35,36]. Smirnova et al identified the infiltration of grafts by activated B cells in a mouse model of chronic rejection, showing that B cells are deeply involved in chronic rejection [37].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that B cells have multiple functions, including immunoglobulin production, cytokine production, and antigen presentation, therapeutic approaches targeting B-cells are important for controlling AMR [35,36]. Smirnova et al identified the infiltration of grafts by activated B cells in a mouse model of chronic rejection, showing that B cells are deeply involved in chronic rejection [37].…”
Section: Discussionmentioning
confidence: 99%
“…The exact relationship of eosinophil counts and allograft rejection is not fully understood and many investigators are still trying to dissect the complex interaction of key mediators in transplant alloimmunity [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. For several years, we have considered eosinophils as an epiphenomenon highly correlating with lung allograft rejection, which is supported by recent research [ 18 ].…”
Section: Why Consider Eosinophils and Lymphocytes?mentioning
confidence: 99%
“…The final effect is to stop the activation of lymphocyte cells, which generates immunosuppression. In vivo, rapamycin has a direct effect on immune-mediated responses to suppress T- and B-cell activation, such as allograft rejection [ 67 ]. Rapamycin, on the other hand, does not directly block mTOR kinase activity.…”
Section: Mtor Inhibitors: Chemistry and Mechanistic Perspectives On C...mentioning
confidence: 99%